Efficacy and safety of non-invasive neurostimulation for insomnia in adults: protocol of a systematic review and network meta-analysis - Lu, Jinxian; Hu, Jun; Lu, Yi; Zhang, Xuecheng; Wang, Qi; Jia, Hongling; Zhang, Yongchen (Frontiers in Psychiatry, 2025)
BackgroundNon-invasive neurostimulation therapies have demonstrated broad therapeutic potential in the management of insomnia. However, there remains a paucity of systematically integrated evidence regarding the efficacy of commonly used clinical interventions. To address this gap, this study will employ systematic review and network meta-analysis (NMA) to evaluate the comparative efficacy and safety profiles of different non-invasive neurostimulation for insomnia, with the aim of providing evidence-based guidance for clinical decision-making.MethodsThe PubMed/Medline, Web of Science, Embase, CENTRAL, Scopus, and PsycINFO databases will be systematically searched for randomized controlled trials (RCTs) on non-invasive neurostimulation techniques for the treatment of insomnia in adults, published from inception to August 31, 2025, with no language restrictions. The primary outcome measure is the Pittsburgh Sleep Quality Index (PSQI) score. Secondary outcomes include the Insomnia Severity Index (ISI) score, emotional symptoms, quality of life, and incidence of adverse events. Two independent researchers will perform literature screening, data extraction, and risk of bias assessment. The overall quality of evidence will be evaluated using the CINeMA. For NMA, we will use a random-effects model based on the Bayesian approach to integrate direct and indirect evidence. Statistical analysis will be performed using R software, and the consistency and heterogeneity of the model will be tested.DiscussionThis study will provide an up-to-date synthesis of evidence from all relevant RCTs, which is crucial for evaluating the therapeutic potential and adverse effects of non-invasive neurostimulation techniques in insomnia treatment. The findings will offer valuable insights to assist clinicians in optimizing evidence-based practice.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD420251084949.